Association between pre-competition strength and sprint canoe/kayak performance: a mixed-effects analysis of professional Chinese athletes - Chen, Z.; Li, Z.; Zhang, X.; Shen, H.; Yang, L.; Lin, B.; Zhang, X.; Lin, Y. (PLOS ONE, 2026)
This study aimed to examine the associations between pre-competition strength measures and sprint canoe and kayak performance. A post-hoc observational cross-sectional analysis was conducted using official results from the 2023 National Canoe Sprint Autumn Championships (China). Pre-competition strength testing included the one-repetition maximum of the hexagonal deadlift (HDL), bench press (BP), and prone bench pull (PBP), as well as the maximum number of repetitions in the pull-up (PU). Preliminary race results from single-paddler canoe and kayak events were analyzed, including men`s 200-m and 1000-m races and women`s 200-m and 500-m races. A generalized linear mixed-effects model was used to analyze the data (n = 133; 69 men, 64 women). Fixed effects included relative strength (HDL, BP, PBP, and PU), distance (200 m, 500 m, and 1000 m) and their interactions, sex (male and female), modality (canoe and kayak), and body mass. Athlete identity and heat were treated as random effects. The main findings were: (i) The main model revealed that PBP significantly affected 200 m race time (estimate = -16.7%, p < 0.001), but its effect was reduced at 500 and 1000 m (-6% to -1%); (ii) sensitivity analyses indicated that PBP had a greater influence on race time in men (-19.7% to -7.8%) than in women (-10.9% to 2.6%), whereas PU was significant only in women (-0.254%, p = 0.043); (iii) PBP had a stronger impact on race time in kayak than in canoe (-25.7% to -8.3% vs. -8.6%). Although no strength variables reached statistical significance in canoe (p = 0.060-0.239), improvements in PU may still meaningfully contribute to race performance in this modality (95% confidence interval = -0.45% to 0.00935%). Therefore, integrating targeted upper-body resistance training into pre-competition preparation may therefore support improved race outcomes in Chinese professional canoe and kayak athletes.